Pengaruh Kepuasan Kerja, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan - Ian Nurpatria Suryawan; Andia Salsabilla (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
This study aims to analyze and examine the effect of job satisfaction, work discipline and work motivation on the performance of employees of PT. KWS. The research used is descriptive and causal research. The sample used is 80 permanent employees. With non-probability sampling technique, which includes purposive sampling. With the technique of collecting data using a Sioner cake which was processed with IBM statistics 25 as a test tool. The results of the research which show that job satisfaction, work discipline, work motivation on the performance of employees of PT. KWS these matters in order to obtain maximum employee performance.